Microplastics and nanoplastics in cardiovascular disease—a narrative review with worrying links - Zheng, Haixiang; Vidili, Gianpaolo; Casu, Gavino; Navarese, Eliano Pio; Sechi, Leonardo A.; Chen, Youren (Frontiers in Toxicology, 2024)
With the widespread use of plastic products and the increase in waste, microplastics and nanoplastics (MNPs) have become an important issue in global environmental pollution. In recent years, an increasing number of studies have shown that MNPs may have negative impacts on human health. This review aimed to explore the association between MNPs and cardiovascular disease and provide an outlook for future research. Research has shown that there may be a link between MNPs exposure and cardiovascular disease. Laboratory studies have shown that animals exposed to MNPs often exhibit abnormalities in the cardiovascular system, such as increased blood pressure, vascular inflammation, and myocardial damage. Epidemiological surveys have also revealed that people exposed to MNPs are more likely to suffer from cardiovascular diseases, such as hypertension and myocardial infarction. Although the specific impact mechanism is not fully understood, there are several possible pathways of action, including the effects of toxic substances on MNPs and interference with the endocrine system. In summary, MNPs exposure may have a negative impact on cardiovascular health, but further research is needed to confirm its specific mechanism and extent of impact to guide relevant public health and environmental policies.